Delirium superimposed on dementia: a survey of delirium specialists shows a lack of consensus in clinical practice and research studies. (22nd December 2015) - Richardson, Sarah; Teodorczuk, Andrew; Bellelli, Giuseppe; Davis, Daniel H. J.; Neufeld, Karin J.; Kamholz, Barbara A.; Trabucchi, Marco; MacLullich, Alasdair M. J.; Morandi, Alessandro
ABSTRACT: Background: Despite advances in delirium knowledge and the publication of best practice guidelines, uncertainties exist regarding assessment of Delirium Superimposed on Dementia (DSD). An international survey of delirium specialists was undertaken to evaluate current practice. Methods: Invitations to participate in an online survey were distributed by email among members of four international delirium associations with additional publication on their websites. The survey covered the assessment and diagnosis of DSD in clinical practice and research studies. Questions were structured around current practice and attitudes. Results: The 205 responders were mostly confident that they could detect DSD with 60% rating their confidence at 7 or above on a likert scale of 0 (none) to 10 (excellent). Seventy-six percent felt that Dementia with Lewy Bodies (DLB) was the most challenging dementia subtype in which to diagnose DSD. Several scales were used to assess for the presence of DSD including the Confusion Assessment Method (CAM) (54%), DSM-5 criteria (25%) and CAM-ICU (15%). Responders stated that attention (71%), fluctuation in cognitive status (65%), and arousability (41%) were the most clinically useful features to assess when diagnosing DSD. Motor fluctuations were also deemed important but 61% had no specific test to monitor these. Conclusions: The largest survey of DSD practice to date demonstrates that despite good levels of confidence in recognizing DSD, there exists a lack of consensus concerning assessment and diagnosis globally. These findings suggest the need for the development of more research leading to precise diagnostic criteria and comprehensive guidelines regarding the assessment and diagnosis of DSD.